Recordar lo que fuimos, pensar lo que somos: una aproximación al documental Volver a vernos (Rodríguez Sickert, 2002) - Aimaretti, María (2025)
From the theoretical-methodological tools of memory studies and documentary film, this article analyzes the film Pinochet’s Children, by Paula Rodríguez Sickert (2002), in order to think about the forms of representation of intra- and intergenerational encounters in the political Chilean documentary of the 21st century. The case is original because it distances itself from the trend that will become dominant in the 2000s, focused on the investigation of the repressive-disappearance action of State terrorism, through first-person accounts. Here, however, priority is given to the testimonial fresco and the reconstruction of the experience of those young people who led the fight against the dictatorship in the 1980s —a key historical process and an “intermediate” generation not entirely recovered by local audiovisual production—. We are interested in problematizing the way their voices and memories are staged, observing narrative procedures, iconographies, and soundscapes.